Salicylic acid improves acclimation to salt stress by stimulating abscisic aldehyde oxidase activity and abscisic acid accumulation, and increases Na+ content in leaves without toxicity symptoms in Solanum lycopersicum L - Szepesi, Agnes (Journal of plant physiology, 2009)
Pre-treatment with 10(-4)M salicylic acid (SA) in hydroponic culture medium provided protection against salinity stress in tomato plants (Solanum lycopersicum L. cv. Rio Fuego). The effect of 10(-7) or 10(-4)M SA on the water status of plants was examined in relation to the biosynthesis and accumulation of abscisic acid (ABA) in order to reveal the role of SA in the subsequent response to salt stress. Both pre-treatments inhibited the K+(86Rb+) uptake of plants, reduced the K+ content of leaves, and caused a decrease in leaf water potential (psi(w)). Due to the changes in the cellular water status, SA triggered the accumulation of ABA. Since the decrease in psi(w) proved to be transient, the effect of SA on ABA synthesis may also develop via other mechanisms. In spite of osmotic adaptation, the application of 10(-4)M, but not 10(-7)M SA, led to prolonged ABA accumulation and to enhanced activity of aldehyde oxidase (AO1, EC.1.2.3.1.), an enzyme responsible for the conversion of ABA-aldehyde to ABA, both in root and leaf tissues. AO2-AO4 isoforms from the root extracts also exhibited increased activities. The fact that the activities of AO are significantly enhanced both in the leaves and roots of plants exposed to 10(-4)M SA, may indicate a positive feedback regulation of ABA synthesis by ABA in this system. Moreover, during a 100mM NaCl treatment, higher levels of free putrescine or spermine were found in these leaves or roots, respectively, than in the salt-stressed controls, suggesting that polyamines may be implicated in the protection response of the cells. As a result, Na+ could be transported to the leaf mesophyll cells without known symptoms of salt toxicity